Study the Genotoxicity of Aqueous and Alcoholic Extracts of Adhatoda Vasica on the Roots of Allium cepa L. by RAPD-PCR Technique (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Molecular technique RAPD-PCR used to detect the genotoxicity of different concentrations of aqueous and alcoholic extracts of Adhatoda vasica leaves on onion Allium cepa L. roots. Five concentrations (1%, 2%, 3%, 5%, and 7.5%) and (10%, 15%, 20%, 30% and 40%) were adopted for alcoholic and aqueous extracts respectively. Ten arbitrary primers used in this study, only eight showed polymorphic bands in the gel and two primers were neglected because they did not show any polymorphic bands for all samples. The aim of this study is to detect the toxic effect of the extracts on the root of onion. The emergence and disappearance of bundles in the genome of onion plant Allium cepa L. Treatment with extracts was studied. The genetic relationship tree was established and the genetic distance calculated based on the results obtained from the gel electrophoresis to clarify the toxic effects of the extracts .The results showed that the concentrations that gave the highest effect and the most toxic for aqueous extract is 40% and for the alcoholic extract is 7.5% which are recommended as effective concentrates if used as a pesticide.